Nivel de dependencia y calidad de vida de los adultos mayores del centro gerontológico Hogar Santa María Josefa de Macará periodo 2022 - Villalta Gutiérrez, Leidy Mabel (2022)
The ageing process entails a series of changes and functional declines which can undermine the capacity to maintain autonomy and this in turn has implications and seriously compromises the life quality. This research aimed to determine the relationship between the level of dependency and the life quality of the older adults of the gerontological centre "Hogar Santa María Josefa" in Macará. A cross-sectional, descriptive-correlational methodology was used, with a quantitative approach. The sample consisted of 27 older adults, and the instruments used were the Barthel Index and the FUMAT quality of life scale. The data analysis was carried out applying the Statistical Product and Service Solutions (SPSS) software. The results obtained demonstrated that there is a significant correlation between the two variables, the higher the level of dependence, the lower the level of quality of life. Similarly, levels of dependence in older adults were found, with total and moderate dependence being the most prevalent. Regarding life quality, a low life quality level was predominant among the population. Finally, an intervention plan was designed aimed at strengthening and/or maintaining the functionality of older adults to improve their life quality